2013
DOI: 10.1103/physrevlett.111.046603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transverse Magnetic Anisotropy on Current-Induced Spin Switching

Abstract: Spin-polarized transport through bistable magnetic adatoms or single-molecule magnets (SMMs), which exhibit both uniaxial and transverse magnetic anisotropy, is considered theoretically. The main focus is on the impact of transverse anisotropy on transport characteristics and the adatom's or SMM's spin. In particular, we analyze the role of quantum tunneling of magnetization (QTM) in the mechanism of the current-induced spin switching, and show that the QTM phenomenon becomes revealed as resonant peaks in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…This high sensitivity to the bias has been discussed in Ref. [48] for intrinsic anisotropy, see in particular Fig. 2 of that reference (compare black dashed and solid lines of the bottom plots).…”
Section: F Spin-filtering Effectsupporting
confidence: 68%
See 2 more Smart Citations
“…This high sensitivity to the bias has been discussed in Ref. [48] for intrinsic anisotropy, see in particular Fig. 2 of that reference (compare black dashed and solid lines of the bottom plots).…”
Section: F Spin-filtering Effectsupporting
confidence: 68%
“…The non-linear conductance is obtained using the leading order perturbation theory (Fermi golden rule) and a master equation, for details see Refs. [46][47][48]. In Fig.…”
Section: Identification Of Quadrupolar Term From Transport Spectramentioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies have demonstrated that the presence of nonzero transverse anisotropy modifies the switching frequency of few-atom magnets when atoms are directly adsorbed on the substrate [7]. It has also been predicted that finite values of transverse anisotropy lead to the appearance of peaks in the differential conductance when using spin-polarized STM [21], and a recent experiment has demonstrated that the strength of the magnetocrystalline anisotropy can be controllably enhanced or reduced by manipulating its local strain environment [22]. In addition, ferromagnetically coupled atomic chains (nanomagnets) usually exhibit non-negligible values of transverse anisotropy [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Crystals of SMMs have drawn attention due to unique quantum properties such as quantum tunneling of magnetization 1,2 and quantum interference or Berry-phase oscillations induced by the magnetic anisotropy [4][5][6] . There have been studies of the interplay between the quantum properties and the electron transport of individual SMMs at the single-molecule level [7][8][9][10][11][12][13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%